The role of copper in bifacial CdTe based solar cells - Khrypunov, G.; Meriuts, A.; Shelest, T.; Deineko, N.; Klyui, N.; Avksentyeva, L.; Gorbulik, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
We present an innovative back contact for CdTe solar cell by the application of a transparent conducting oxide, typically ITO, as a back electrical contact on CdTe/CdS photovoltaic devices that acts as a free-Cu stable back contact and at the same time allows to realize bifacial CdTe solar cells, which can be illuminated from either or both sides. The controlled insertion of a very limited amount of copper into the ITO back contact permits to have reproducible devices with high efficiencies still keeping the bifacial configuration. Thin CdTe layer solar cells with ITO back contact have been realized with efficiencies exceeding 10%, the reduced thickness of CdTe allows to have a better performance on the back-side illumination and reduces the amount of CdTe material.